Characterization of carbapenem-resistant Gram-negative bacteria from Tamil Nadu. (2nd September 2016) - Nachimuthu, Ramesh; Subramani, Ramkumar; Maray, Suresh; Gothandam, K. M.; Sivamangala, Karthikeyan; Manohar, Prasanth; Bozdogan, Bülent
Abstract : Carbapenem resistance is disseminating worldwide among Gram-negative bacteria. The aim of this study was to identify carbapenem-resistance level and to determine the mechanism of carbapenem resistance among clinical isolates from two centres in Tamil Nadu. In the present study, a total of 93 Gram-negative isolates, which is found to be resistant to carbapenem by disk diffusion test in two centres, were included. All isolates are identified at species level by 16S rRNA sequencing. Minimal inhibitory concentrations (MICs) of isolates for Meropenem were tested by agar dilution method. Presence of bla OXA, bla NDM, bla VIM, bla IMP and bla KPC genes was tested by PCR in all isolates. Amplicons were sequenced for confirmation of the genes. Among 93 isolates, 48 (%52) were Escherichia coli, 10 (%11) Klebsiella pneumoniae, nine (%10) Pseudomonas aeruginosa. Minimal inhibitory concentration results showed that of 93 suspected carbapenem-resistant isolates, 27 had meropenem MICs ≥ 2 μg/ml. The MIC range, MIC50 and MIC90 were < 0.06 to >128 μg/ml, 0.12 and 16 μg/ml, respectively. Fig.1 . Among meropenem-resistant isolates, E. coli were the most common (9/48, 22%), followed by K. pneumoniae (7/9, 77%), P. aeruginosa (6/10, 60%), Acinetobacter baumannii (2/2, 100%), Enterobacter hormaechei (2/3, 67%) and one Providencia rettgeri (1/1, 100%). PCR results showed that 16 of 93 carried bla NDM, three oxa181, and one imp4 . Among bla NDM carriers, nine were E. coli, four Klebsiella pneumoniae, two E. hormaechei and one P. rettgeri . Three K. pneumoniae were OXA-181 carriers. The only imp4 carrier was P. aeruginosa . A total of seven carbapenem-resistant isolates were negatives by PCR for the genes studied. All carbapenem-resistance gene-positive isolates had meropenem MICs >2 μg/ml. Our results confirm the dissemination of NDM and emergence of OXA-181 beta-lactamase among Gram-negative bacteria in South India. This study showed the emergence of NDM producer in clinical isolates of E. hormaechei and P. rettgeri in India.